Estudos para a disponibilização de metodologias de avaliação da qualidade de grãos de café - Cardoso, Danilo Barbosa (2016)
The production and trading of coffee grains depend on quality evaluation, which is conducted by means of mandatory tests and analyses, of which results must guarantee the identity, origin and minimum quality demanded. However, currently, these evaluations are done by people, with the results being susceptible to subjectivity. In this context, the availability of quick, simple, trustworthy, economic and of easy standardization tests and analyses to the producers, contributing for the improvement of the productive processes, is of paramount importance for the sustainability of coffee agribusiness. The analysis of images has been highlighted as a non-destructive, quick, objective and extremely efficient technique for analyzing the quality of not only seeds, but also grains. Among the techniques evaluated in this work, ultra-weak light decay detection (DL) has presented high potential for evaluating the quality of grains from other cultures, with the advantage of consisting of a non-destructive method. Another technique associated to computer programs that use image analysis is the SAS equipment (Seeds Analysis System), specifically developed for the visual analysis of seeds, grains and plantlets. After obtaining the samples made available by Cooxupé, sensorial analysis were conducted according to SCAA and IN 8 protocol, evaluation using the SAS, evaluation of DL behavior and chemical analyses. Posteriorly, the data were analyzed to identify the possible relation between the collected information and the quality of the beverage. Despite the new equipment used in this work having showed good use for evaluating other quality parameters of the lots of raw grain, these parameters have no direct relation to the final quality of the beverages.